Investigating the Genuineness of Suicide Notes in Social Media - Widiatmika, Putu Wahyu; Pastika, I Wayan; Satyawati, Made Sri (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
This study aims to find linguistic evidence that is able to act as legal evidence in determining the genuineness of a suicide note. The data sources were written and digital suicide notes from Indonesia. The data were collected from social media through documentation. The data collected were graphology and lingual units that indicate the linguistic features of a genuine suicide note. The units were seen from their structure, meaning, and context to determine the motivation. The data were analyzed through referential identity, orthography identity, and distributional methods from descriptive-qualitative and descriptive-quantitative approaches based on linguistic theories. The theories applied were intertextuality, meaning, linguistic features of suicide notes, the context of the situation, and generative transformation. The findings show that written and digital suicide notes, as well as posts on the victim’s social media, provide evidence that the note is genuine and written by the victim. The evidences are recursive graphology, interrelated propositions, and linguistic features of a genuine suicide note. The motivations for suicide are derived from the victim’s self-blaming, his acknowledgment of his inability to help himself from financial and mental issues, and a constant feeling of being a disappointment to people who had supported him.